The characteristics of recycled NO reduction over char during oxy-fuel fluidized bed combustion. (15th March 2017) - Xu, Mingxin; Li, Shiyuan; Wu, Yinghai; Jia, Lufei; Lu, Qinggang
Highlights: Reduction of recycled NO during char oxy fluidized bed combustion was investigated. Char combustion could promote the reduction of recycled NO over char. Concentration of recycled NO had little effect on the reduction of recycled NO. Recycled SO2 could enhance the recycled NO reduction. Low concentration of recycled CO played little effects on the recycled NO reduction. Abstract: To explain the reduction process of recycled NO over char during oxy-fuel fluidized bed combustion, the characteristics associated with the reduction of recycled NO were investigated in the present study. The experimental results were obtained using a bubbling fluidized bed. The effects of typical impurities within the recycled flue gas on the reduction of recycled NO were also studied. It was determined that significant reduction of the recycled NO over char occurred under oxy-fuel fluidized bed combustion conditions. The apparent activation energy of the recycled NO reduction reaction was much lower when combustion occurred. The competition between the NO formation from char nitrogen and the reduction of recycled NO over char determined the final NO concentration of the flue gas. The recycled NO concentration had little influence on the reduction ratios during oxy-fuel fluidized bed combustion when NO formation from char nitrogen was considered. Recycled SO2 can enhance the reduction of recycled NO over char during oxy-fuel combustion while the low concentration of recycled CO had a little effect on the process of recycled NO reduction. The reduction ratios of recycled NO increased as the recycled SO2 concentration increased. Moreover, significant capture of recycled SO2 was observed during oxy-fuel fluidized bed combustion.